Just for the summer : a novel [large type] - Carlson, Melody (Thorndike Press large print Christian fiction series., 2024)
"Ginny Masters manages a popular boutique hotel in Seattle, but the daily challenges and irritations of a fast-paced job and a demanding boss are starting to get to her. Jacqueline Potter manages her grandfather's fishing lodge in Idaho because it was the only job she could find after graduating with her hospitality degree. She's grateful for the work but longs for a more sophisticated and cosmopolitan life she's just not going to find in this backwoods town. The solution to both their problems seems obvious. Just for the summer, they'll swap jobs and lifestyles. But they'll soon find that there's more to finding happiness than just switching up the scenery." --